2008
DOI: 10.1002/hep.22534
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of hepatitis C virus reinfection in a cohort of injecting drug users

Abstract: An estimated 170 million people worldwide carry the hepatitis C virus (HCV), and in more developed countries the prevalence and incidence of HCV is particularly high among injecting drug users (IDUs). Spontaneous clearance of HCV infection and reinfection is well recognized but the level of protection against further infection conferred by HCV infection and clearance remains uncertain. We conducted a prospective study of HCV infection in IDUs recruited in Melbourne, Australia, using a much shorter median testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
116
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 23 publications
13
116
0
Order By: Relevance
“…Although both viruses are associated with chronic infections, unlike HIV, HCV can be spontaneously cleared by the host. This may explain in part the differences in the number of recombinants between HIV and HCV, where partial protective immunity against the latter reduces that chance of in vivo recombination of HCV strains (1,43,69). However, the high rate of mixed infections observed suggests that this is likely at best to play a minor role in HCV recombination.…”
Section: Figmentioning
confidence: 99%
“…Although both viruses are associated with chronic infections, unlike HIV, HCV can be spontaneously cleared by the host. This may explain in part the differences in the number of recombinants between HIV and HCV, where partial protective immunity against the latter reduces that chance of in vivo recombination of HCV strains (1,43,69). However, the high rate of mixed infections observed suggests that this is likely at best to play a minor role in HCV recombination.…”
Section: Figmentioning
confidence: 99%
“…The number of new infections per year is therefore given by so that per year. There is debate about the rate of reinfection in those that have previously cleared infection with estimates ranging from 2% to 47% per year (Aitken et al, 2008a;Backmund et al, 2004;Grebely et al, 2006). We assume a reinfection rate, of 5% per year thus but acknowledge that new research suggests it is higher than this.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…And, P11=P44, P12=P42, P13=P43, P17=P27=P37=P47= P57=P67=μ and for k=1,…, (27, Some research has found that following spontaneous clearance of an acute infection a proportion of individuals may have protective immunity to re-infection; however, findings regarding a conferring of a protective immunity are equivocal [40][41][42][43]. In order to capture the possibility of some level of a protective immunity, a corresponding state (z) was included in the natural history model with a low transition probability (0.25) [19].…”
Section: Quasi-markov Model Transition Probabilities and Parametersmentioning
confidence: 99%